Structural investigation of silicon nanowires with grazing incidence small angle X‐ray scattering. (1st October 2013) - Buttard, Denis; Schülli, Tobias; Oehler, Fabrice; Gentile, Pascal
Abstract : Presented is a structural investigation of silicon nanowires, which is conducted with grazing incidence small angle X‐ray scattering. The morphology of the wires is analysed following experimental measurements. Three diameters (50, 100 and 200 nm) are investigated in relation to the aspect ratio of the wires (length 25 µm). Periodic fringes because of the weak distribution of the diameter are observed on the experimental images. The asymptotic behaviour of the scattering signal along the qy direction is also analysed and presented.